2021
DOI: 10.1101/2021.07.02.450964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Nsp14 mediates the effects of viral infection on the host cell transcriptome

Abstract: To identify functions of SARS-CoV-2 proteins, we performed transcriptomic analyses of cells expressing individual viral proteins. Expression of Nsp14, a protein involved in viral RNA replication, provoked a dramatic remodeling of the transcriptome that strongly resembled that observed following SARS-CoV-2 infection. Moreover, Nsp14 expression altered the splicing of more than 1000 genes and resulted in a dramatic increase in the number of circRNAs, which are linked to innate immunity. These effects were indepe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…A considerable feature of MERS-CoV and SARS-CoV is the production of double-layered membrane vesicles (DMVs) that the processes of transcription occur within them [45] . Additionally, autopsy and histopathological investigation of the kidney tissue in patients with COVID-19 indicated that SARS-CoV-2 might exist inside the DMVs of the host cells [46] .…”
Section: Resultsmentioning
confidence: 99%
“…A considerable feature of MERS-CoV and SARS-CoV is the production of double-layered membrane vesicles (DMVs) that the processes of transcription occur within them [45] . Additionally, autopsy and histopathological investigation of the kidney tissue in patients with COVID-19 indicated that SARS-CoV-2 might exist inside the DMVs of the host cells [46] .…”
Section: Resultsmentioning
confidence: 99%
“…While facilitating viral replication by contributing to RTC assembly, SARS-CoV-2 non-structural proteins, including Nsp9 and Nsp14, directly affect the host cell transcriptome (Zaffagni et al, 2022). In this way SARS-CoV-2 has a direct effect on the transcriptional profile of infected cells (Blanco-Melo et al, 2020;Chakraborty et al, 2021;Sun et al, 2021;Wyler et al, 2021).…”
Section: Nsp23 Nanobody Treatment Blocks Viral Replication Of Sars-co...mentioning
confidence: 99%
“…The proviral action of the immune factor ISG15 leads to the generation of an autocrine loop, which amplifies and prolongs autocrine signalling and ultimately induces viral drug resistance ( 89 , 90 ). Furthermore, the S protein of SARS-CoV-2 can prevent the virus from being cleared by immune factors, and mutation of the S protein will further enhance the ability of the virus to evade immune responses ( 91 , 92 ). In addition, the expression of viral nsp14 can upregulate the levels of circRNAs related to innate immunity, thereby inhibiting viral replication and immune evasion ( 93 ).…”
Section: Potential Mechanisms Of Circrnas In Sars-cov-2 Infectionmentioning
confidence: 99%
“…For example, Zaffagni M et al. ( 92 , 96 ) found that SARS-CoV-2 Nsp14 mediates the effects of viral infection on the host cell transcriptome. Nsp14 altered the splicing of more than 1000 genes and resulted in a dramatic increase in the number of circRNAs that were linked to innate immunity.…”
Section: Potential Mechanisms Of Circrnas In Sars-cov-2 Infectionmentioning
confidence: 99%